Design and fabrication of dual axis solar system tracker - Muhammad Amir Syahiran, Muhammad Tarminzi (2016)
Solar power is the energy from the sun that is converted into thermal or electrical energy. The uses of solar energy are now developing rapidly since it is the cleanest and renewable energy source available. This paper presents the design and fabrication of high-efficiency dual-axis solar tracking system. Moreover, the objectives of this paper is to make sure the designed dual-axis solar tracking system can move the solar panel to the direction of the light accurately. The project can be divided into two stages, which are the designing the structure of the solar tracker and the fabrication of the parts. In the design development, SolidWorks software is used to create the structure of the solar tracking system. To prove the structure is perfect for the solar tracking system, another software is used to test it. For the fabrication part, correct process is carefully chosen based on the machines and tools available in UMP. After the structure is completed, a solar panel, two linear actuators, sensors and batteries are assembled in the solar tracking system. The efficiency of the system has been tested and compared with static solar panel on several time intervals, and it shows the system react the best at the to-minutes intervals with consistent voltage generated. Therefore, the structure has been proven working for directing the solar panel towards the direction of light accurately so that it can capture maximum sunlight source for high efficiency solar harvesting applications.